Empowerment of Tribal Children in the Field of Education by Friends of Child Exploration (SEAD) Jambi : A Functional Structural Perspective - Putri, Titania Orea; Malihah, Elly; Komariah, Siti (Universitas Pendidikan Mandalika, 2024)
This research aims to describe the process of empowering tribal children in the field of education carried out by Friends of Child Exploration (SEAD) in Jambi. The method used in the research was a qualitative approach with a case study method. The selection of informants was carried out using a purposive sampling technique to select informants consisting of 9 key informants, namely volunteer friends exploring children in Jambi and also Waris from the Anak Dalam tribe, as well as five supporting informants, namely Tumanggung, parents from the Anak Dalam tribe and also the community. The data collection techniques used were observation, in-depth interviews and documentation studies. Data analysis was done through data reduction, presentation, and conclusion. This research also used data triangulation techniques to test the validity of the data. The findings of this research were that empowerment in education provides a way for tribal children to learn how to read, write and count. If we look at the empowerment process carried out by the Deep Child Exploration Friends (SEAD) Jambi for children from the inner child tribe, the teaching and learning process begins with an introduction stage for all children of different ages after new material improvements have been made. What will be taught is differentiated from children's material, which is still in the introductory stage. Apart from that, if we look at the planning carried out by Jambi Children's Exploration Friends (SEAD), it is always adjusted to the situation and conditions in the field. There is no element of coercion, but it is carried out with a first approach and adaptation to the children, such as by teaching them to play first, eat and sing together. In the teaching and learning process, the methods used are also adapted to the children so that they are not boring and always look for ways to keep them happy during the empowerment activities.